Mirabegron escalation to 50 mg further improves daily urgency and urgency urinary incontinence in Asian patients with overactive bladder - Chun-Hou Liao (Journal of the Formosan Medical Association, 2019)
Purpose: To investigate the efficacy and safety of mirabegron dose escalation from 25 to 50 mg in Asian patients with overactive bladder (OAB). Methods: A total of 242 patients (mean age: 67 years) with OAB were randomized to two groups: M25 (mirabegron 25 mg daily for 12 weeks) and M50 (mirabegron 25 mg daily for 4 weeks + 50 mg daily for 8 weeks). The primary endpoint was the percentage of patients without urgency or with a reduction of ≥2 in daily urgency episodes after treatment. Secondary endpoints included OAB symptom scores and other voiding parameters. Chi-squared and Wilcoxon signed-rank tests were used for data comparison. Results: All OAB symptom scores in both groups improved significantly at 4 and 12 weeks. Both groups showed similar numbers of patients who reached the primary endpoint after treatment (M25: 64.6%, 42/65; M50: 64.9%, 50/77; p = 0.554). Patients in the M50 group with residual daily urgency or urgency urinary incontinence (UUI) episodes after 4 weeks of mirabegron 25 mg had a significantly higher rate of reduction in daily urgency episodes (60.9% vs. 34.5%, p = 0.034) and daily UUI episodes (87.5% vs. 37.5%, p = 0.021). Adverse event (AE) rates were similar between the groups. Conclusion: Mirabegron 25 mg for 12 weeks and mirabegron dose escalation from 25 to 50 mg exerted similar therapeutic effects. However, the dose escalation further improved the daily urgency and UUI episodes in patients with residual urgency or UUI after the initial treatment with mirabegron 25 mg. Keywords: Urinary bladder, Overactive, Adrenergic beta-3 receptor agonists